PSYCHIC HEALTH PROTECTION IN NATIVE CHILDREN OF TYVA REPUBLIC - I.P. Artyukhov; V.T. Manchuk; N.B. Semenova ("Paediatrician" Publishers LLC, 2009)
The article represents organizational - functional pattern of optimization of social psychic and medical pedagogical assistance for native children and adolescents in Tyva Republic. The pattern is aimed at psychic health improvement and prophylaxis against non-adaptable forms of conduct. It is based on complex approach to providing assistance to children and adolescents, preventive measures and the increase in the quality of medical assistance.Key words: Children, psychic health, non-adaptable conduct, prophylaxis(Voprosy sovremennoi pediatrii - Current Pediatrics. 2009;8(2):12-15)